Commumity Structure of Benthic Macroinvertebrates and Species Diversity of Caddisfly Adults in Sahakornnikom Sub-district, Thong Pha Phum District, Kanchanaburi Province during the New Normal Tourism - Sangpradub, Narumon; Hanjavanit, Chutima; Rattanawilai, Kwansiri; Phlai-ngam, Sirikamon; Tevapawat, Patipat; Somnark, Rungnapa; Vannachak, Viengkhone (KKU Science Journal, 2023)
Benthic macroinvertebrates are aquatic animals that live on or just below the stream-bed. They are important in detrital process and as food source for fish, other aquatic animals as well as terrestrial animals such as birds and bats. Thus, they play a critical role in the balance and natural flow of energy and nutrients. In the present study, benthic macroinvertebrate community structure and species diversity of caddisfly adults were explored in natural tourist attractions at Dr. Phol Kleepbua mine tunnel, stream beside the tunnel, mountain water supply weir and Saphanlao Waterfall in Sahakornnikom Sub-district, Thong Pha Phum District, Kanchanaburi Province. The field samplings were conducted in November 2021 and March 2022 which was the New Normal tourism period with very few tourists. A total of 121 taxa in 58 families of benthic invertebrates were found. The streams beside the tunnel and the Saphanlao Waterfall had more diversity and abundance of benthic macroinvertebrates than those of the access point into the tunnel and mountain water supply weir. Most of them were aquatic insects in the orders Trichoptera (Caddisfly), Ephemeroptera (Mayfly) and Diptera (True fly). Freshwater snails were found only at Saphanlao Waterfall. The diversity and abundance of benthic invertebrates in March 2022 was higher than November 2021, except at the stream beside the tunnel as some waterways were dried up due to naturally low water levels which decreased the animal's habitat. Benthic macroinvertebrate community structure between streams beside the tunnel and Saphanlao Waterfall, was similar about 61%; the main source of carbon entering ecosystems is from terrestrial ecosystems (allochthonous). The highest proportion of filtering-collectors suggest that the majority of available diets for benthic macroinvertebrates are fine particular organic matter (FPOM) that transported by water current. Thirty-five species in 10 families of caddisfly adults were found; most of them in families Hydropsychidae and Philopotamidae were corresponded to the larval stage. Biological assessment of water quality showed that the stream beside the tunnel had better water quality than Saphanlao Waterfall. The results from this study will be used as a baseline to compare future changes with increased tourism activities. Each studied site served as a genetic preservation site for benthic macroinvertebrates. The existence of these natural resources depends on the surrounding forests, which provide habitat, shade, and energy sources for stream ecosystems. Therefore, protecting the surrounding forests is essential to the sustainability of the site and contributes to Goal 15 (Lives on Land) of the Sustainable Development Goals.